Outcomes of Newly Diagnosed Acute Myeloid Leukemia Patients Treated With Hypomethylating Agents With or Without Venetoclax: A Propensity Score-Adjusted Cohort Study - Mustafa Ali, Moaath K.; Corley, Elizabeth M.; Alharthy, Hanan; Kline, Kathryn A. F.; Law, Jennie Y.; Lee, Seung Tae; Niyongere, Sandrine; Duong, Vu H.; Emadi, Ashkan; Baer, Maria R. (Frontiers in Oncology, 2022)
There is a deficiency of real-world data on the impact of combining venetoclax (VEN) with hypomethylating agents (HMAs) in newly diagnosed acute myeloid leukemia (AML) patients. We conducted a single-center, propensity-adjusted retrospective cohort study to compare composite complete remission (CCR) rates, median overall survival (m-OS) and median event-free survival (m-EFS). A total of 170 adult AML patients were treated with first-line azacitidine (AZA) or decitabine (DEC) +/- VEN. Median age was 71 years and 99 (58%) were male. Median follow-up in HMA and HMA-VEN groups was 79 and 21 months. Treatments included AZA alone (n=35, 21%), DEC alone (n=84, 49%), AZA-VEN (n=24, 14%) and DEC-VEN (n=27, 16%). VEN improved CCR rates to HMAs overall (52% vs. 27%, P<0.05) and to AZA (54% vs. 10%, P<0.05), but not to DEC (43% vs. 32%, P=0.35); it did not improve OS, and only improved EFS for AZA (10.5 vs. 3.8 months, P<0.05). CCR rates were lower with AZA than with DEC (13% vs. 33%, P<0.05), but OS and EFS were not different statistically. CCR rates did not differ for AZA-VEN vs. DEC-VEN (CCR: 58% vs. 52%, P=0.66), but OS and EFS were longer for AZA-VEN (m-OS: 12.3 vs. 2.2 months, P<0.05; m-EFS: 9.2 vs. 2.1 months, P<0.05). Our analysis showed that combining VEN with AZA in newly diagnosed AML patients improved outcomes, but combining VEN with DEC did not. AZA-VEN was was associated with improved outcomes compared to DEC-VEN. Further studies are needed to test the benefit of combining VEN with DEC.